2020
DOI: 10.1021/acs.chemmater.9b04714
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bond Formation of Brønsted Acid Sites in Zeolites

Abstract: Brønsted acid sites (BAS) in dry aluminosilicate zeolites, also known as bridging O H −H groups, may form hydrogen bonds with other framework oxygen atoms, O, in addition to BAS that are free of such interactions. These are referred to as perturbed and unperturbed BAS, respectively. However, hydrogen bonding may occur only for specific geometric orientations between two framework oxygen atoms, allowing an O H −H•••O interaction. To evaluate the possibility for such hydrogen bonding, we introduce an alignment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
134
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(159 citation statements)
references
References 67 publications
8
134
1
10
Order By: Relevance
“…[46][47][48][49] H4 corresponds to acid sites with enhanced acidity tentatively associated with isolated Brønsted sites (AlOHSi). [50] In our case,H4isnot related to any ammonium residue as the { 1 H}-15 NCPNMR spectrum does not show any ammonium cations,i na greement with the zeolite IR spectrum where the characteristic deformation vibration band of ammonium at 1455 cm À1 is absent, Figure S7. [16] Ther emaining signal at 2.6 ppm corresponds to extra-framework aluminum species H EFAL .…”
Section: Hm As Nmr Spectroscopysupporting
confidence: 46%
See 1 more Smart Citation
“…[46][47][48][49] H4 corresponds to acid sites with enhanced acidity tentatively associated with isolated Brønsted sites (AlOHSi). [50] In our case,H4isnot related to any ammonium residue as the { 1 H}-15 NCPNMR spectrum does not show any ammonium cations,i na greement with the zeolite IR spectrum where the characteristic deformation vibration band of ammonium at 1455 cm À1 is absent, Figure S7. [16] Ther emaining signal at 2.6 ppm corresponds to extra-framework aluminum species H EFAL .…”
Section: Hm As Nmr Spectroscopysupporting
confidence: 46%
“…TheNMR study clearly showed that in contrast to Y, USY displays extremely high acidic sites (H4 sites) that might correspond to isolated Brønsted sites (AlOHSi). [50] These acid sites are absent in Y. Theshortening of the diffusion pathlengths,i.e., the additional mesoporosity introduced during stabilization, is also present, but it is not the major factor for this high performance.T oe xclude this possibility,ahomemade nanosized zeolite,n ano-Y (70 nm particle size,referred to as Y-70 in the original report), [53] with as imilar framework (Si/Al = 1.7) composition is tested in…”
Section: Discussionmentioning
confidence: 99%
“…The NMR parameters extracted from this data are listed in Table 2. Although we used two lines for 1 H, it must be understood as a continuous distribution of 1 H environments arising from a broad range of Si(OH)Al hydrogenbonded Brønsted acid sites [48][49][50] and possibly Al(OH)Al sites. 51 This asymmetric distribution, ranging from 0 ppm to 10 ppm with a maximum at 2.6 ppm, is similar for all three coordination states of aluminum.…”
Section: Sitementioning
confidence: 99%
“…[3f, 4] BAS can also form hydrogen bonds when suitable OÀ O distances and mutual alignments of O atoms exist. [5] A hydrogen bond is defined [6] by a 1 H chemical shift that is deshielded from the unperturbed BAS at typically 4 ppm. Here, we employ a combination of solid-state NMR methods and DFT calculations of zeolite cluster models for zeolite SSZ-42.…”
mentioning
confidence: 99%